The Impact of E-Cigarettes on Endothelial Function and Cardiovascular Disease Risk - Modliborska, Magdalena; Rucki, Michał; Cieleban, Nikodem; Rucka, Aleksandra; Kowalski, Mateusz; Gajewska, Maja (Journal of Education, Health and Sport, 2026)
Background: Electronic cigarettes (e-cigarettes) are now the most widely used inhalational nicotine product among adolescents and young adults. Although marketed as safer than combustible tobacco, accumulating evidence indicates that vaping injures the vascular endothelium and elevates cardiovascular disease (CVD) risk. Aim: This review synthesizes current evidence on how e-cigarette aerosol affects endothelial function and the resulting cardiovascular consequences, with attention to mechanism, population outcomes, and special populations. Material and methods: PubMed, MEDLINE, Google Scholar, JEHS, and Quality in Sport were searched for peer-reviewed publications between 2015 and 2026, combining "e-cigarette" or "vaping" with terms for endothelial function, flow-mediated dilation, and cardiovascular outcomes. Results: E-cigarette aerosol carries nicotine, propylene glycol and vegetable glycerin thermolysis products, flavorings, and metals leached from heating coils. Acute use raises pulse-wave velocity by approximately 0.26 m/s and heart rate by about 5 beats/min. Chronic users show flow-mediated dilation reduced to roughly 5% versus 11% in non-users. Mechanisms include eNOS uncoupling, NADPH-oxidase activation, formaldehyde-driven TRPA1 signaling, flavoring-induced inflammation, and increased platelet reactivity. Daily vaping was associated with self-reported myocardial infarction in NHIS data (OR 1.79, 95% CI 1.20–2.66); dual use carried higher CVD odds than exclusive smoking (OR 2.56, 95% CI 2.11–3.11). Conclusions: E-cigarettes are not cardiovascularly neutral. They impair endothelial function through multiple, partially nicotine-independent pathways and are associated with adverse cardiovascular outcomes, particularly in dual users and youth.